Administrasi Berbasis Digital dalam Pengelolaan Sekolah: Transformasi dan Implikasinya Terhadap Efisiensi Pendidikan - Giska Helsian; Rahma Dini (Universitas Serambi Mekkah, 2025)
This study aims to analyze the role of school leadership in fostering innovation to improve teacher performance in elementary schools. School principals play a crucial role in creating an environment that supports teacher development through effective clinical supervision and the use of technology in school administration. By adopting transformational and instructional leadership approaches, school principals can motivate teachers to implement innovative teaching methods and enhance the quality of instruction. This research uses a literature review approach by examining relevant articles and journals published in the past seven years. The findings reveal that school principals with a clear vision and strong managerial skills can overcome challenges in implementing innovation, as well as utilize digital-based administration to monitor teacher performance more efficiently. Furthermore, clinical supervision conducted regularly and based on constructive feedback can improve teachers' teaching skills. This study provides valuable insights for school principals and educational institutions to encourage innovation in learning to improve the quality of education in elementary schools.